Comparison of Changes in Rso2 in Midazolam and Propofol Sedation Post Craniotomy in the Icu of H. Adam Malik Hospital - Pratama, Dicko Kanugrahan; Irina, Rr Sinta; Winata, Ade (Jurnal Neuroanestesi Indonesia, 2024)
Introduction: Cerebral oxygen saturation reflects tissue perfusion in the cerebrum. Decreases in cerebral oxygen saturation are linked to longer hospital stays and cognitive impairment. Midazolam and propofol can decrease cerebral blood flow through decreasing the cerebral oxygen metabolic rate. The purpose of this research is to analyze the comparison of changes in cerebral oxygen saturation after midazolam and propofol administration in post-craniotomy patients in the ICU of Haji Adam Malik General Hospital Medan.Subject and Method: This is a randomized control trial study. Patients were divided into, Midazolam group, that given an initial dose of 0.05 mg/kg followed by a maintenance dose of 0.02-0.10 mg/kg/hour and Propofol group that given sedation with a dose of 0.3-3mg/kg/hour, with the target of the 2 groups being a Richmond Agitation-Sedation Scale (RASS) value of 0 to -2. Data analysis using unpaired T test.Results: The results for cerebral regional oxygen saturation and RASS between groups showed significant differences in right and left value (p 0.001), but there was no significant difference in RASS (p0.05) between each group at each measurement time. The results of the analysis of cerebral regional oxygen saturation and RASS between times, there was no significant difference in right and left value (p0.05), but there was a significant difference in RASS (p0.001) at each measurement time. Based on the results of the analysis carried out, it is known that there is no statistically significant difference in changes in cerebral regional oxygen saturation both right and left in changes in RASS because it is found that all data have p0.05.Conclusion: There is no change in right and left for cerebral regional oxygen saturation after administration of propofol and midazolam groups with RASS value 0 to -2 in post-craniotomy patients in the ICU of Haji Adam Malik General Hospital Medan